Scleral Contact Lens for Steven-Johnson Syndrome: A Case Report - Tri Rahayu; Nurani Rahma Aarafah (Majalah Oftalmologi Indonesia, 2022)
Background: Steven-Johnson syndrome is one of life-threatening skin abnormality. SJS complication involve multiorgan disfunction such as mucosa, ocular, respiration, and digestive tract. Around 30- 50% of SJS patient experience chronic ocular sequel, which concludes progressive symblepharon, margo palpebral keratinization, trichiasis, entropion, corneal pannus, dry eye syndrome, and persistent epithelial cornea defect. Scleral contact lenses has beneficial in managing SJS patient, on both acute and chronic phases. Methods: A 36-year-old female patient with SJS, presented for eye examination due to unpleasant sensation on both of their eyes and unsatisfactory quality of her vision. She presented high myopia, margo palpebral keratinization with trichiasis and distichiasis, symblepharon and hyperemic conjunctiva, wide corneal scar, and ocular neovascularization. A diagnostic trial set was used in the fitting process, and she was assessed according to standardized fitting methodology. Visual acuity, corneal topography, biometry, and ocular aberrations were evaluated. The follow-up period was 12 months. Results: The best corrected visual acuity was 20/60 with correction lens S – 1.00 D for the left eye (LE) and 20/25 cannot be corrected with correction lens for the right eye (RE). After corneal contact lens fitting, visual acuity was improved to 20/20 and 20/25 for the RE and LE, respectively. The patient wore these contact lenses an average 8 hours a day. The patient’s dry eye complaint was significantly decrease with more comfortable ocular sensation Conclusion: The present case report describes how the patient had scleral contact lens fitted successfully for management of SJS ocular complication. They provided optimal visual quality and restore the patient’s comfort.